KONTRASEPSI VASEKTOMI PRIA: PERSPEKTIF TEOLOGI ETIKA TERAPAN - Vivi Teriviantina; Ferry Simanjuntak (Jurnal Ledalero, 2021)
The Covid-19 pandemic that began in early 2020 has had serious impacts on various aspects of life globally, nationally and locally, including family planning program services in Indonesia. BKKBN, for example, carries out various policies to increase participation in family planning programs to maintain community welfare by anticipating the baby boom during the Covid-19 pandemic. Based on the results of the survey conducted, the interest of men to participate in becoming MOP contraceptive acceptors began to increase. This is certainly a progress where the awareness of men to participate in family planning programs is increasing. The increase in participants occurred because of ‘correct’ knowledge about family planning programs. Before the Covid-19 pandemic, many men and their families did not have adequate knowledge about vasectomy as a method of contraception. Consequently, this caused limited accessibility to contraceptive services and acceptance among men. The main objective of this paper is therefore to provide complete and clear information to men regarding the benefits, impacts and perspectives of applied ethical theology on the use of the vasectomy method of contraception. Methodologically, this study uses a qualitative method by collecting several journals and books related to the formulation of the problem and looking for possible equations to answer this research problem. The expected results are therefore a wider recognition of the important role of health workers, culture, and experienced family planning cadres, as well as a provision of knowledge and direction in socializing the vasectomy method, including understanding the theologically ethical perspectives of vasectomy as a method of contraception.  Key words: Covid-19, Ethical Theological Perspectives, Family Planning Program, Men, Vasectomy.